Anarchy in the UK : the Angry Brigade - Vague, Tom (Edinburgh : AK Press, 1992)
Much more than any small group of individuals, the Angry Brigade was a movement that challenged reaction and state power in all its forms. Vague presents, in his notoriously barbed pop-culture style, the story of Britain's premier revolutionary hooligans